Analysis of Ocular Surface Characteristics and Incidence of Dry Eye Disease in Systemic Lupus Erythematosus Patients Without Secondary Sjögren's Syndrome - Gu, Zhengyu; Lu, Qinyi; Zhang, Ao; Shuai, Zong Wen; Liao, Rongfeng (Frontiers in Medicine, 2022)
Objective: To investigate the differences in ocular surface characteristics, tear film quality, and the incidence of dry eye disease (DED) between Systemic Lupus Erythematosus (SLE) patients and healthy populations. Methods: This age and gender-matched cross-sectional study included 96 SLE patients without secondary Sjögren's syndrome(SS) and 72 healthy subjects .The Ocular Surface Disease Index (OSDI), tear meniscus height (TMH), non-invasive tear film breakup time (NIKBUT), meibography, and tear film lipid layer grade were assessed. A receiver operative characteristic (ROC) curve was constructed to evaluate the predictive value of risk factors. Results: Compared with the control subjects, a significantly greater proportion of SLE patients met the TFOS DEWS II DED diagnostic criteria (34.3% vs 18.1%, P=0.019). SLE patients without SS had higher OSDI scores ( 10.0（4.5,18.0）VS. 5.0（2.5,11.9), P＜0.001), and shorter NIKBUT ( 9.6（6.6,15.0）VS. 12.3（8.4，15.8）, P=0.035).Furthermore, TMH, Tear film lipid layer grade, and Meibomian gland (MG) dropout in SLE patients were worse than those in control subjects (all P＜0. 05). For ROC analysis, the area under curve (AUC), sensitivity and specificity of prediction were 0.915, 75.8% and 92.1% for the combination of SLE disease activity index (SLEDAI) , age and NIKBUT. Conclusions: SLE patients without SS exhibited a higher risk for DED than healthy subjects, and the poorer meibomian gland function in SLE patients may potentially contribute to the development of DED.The combined parameters of SLEDAI, age and NIKBUT showed a high efficiency for the diagonosis of DED in SLE patients, with practical clinical applictaions.